The Distributional Impact of Fiscal Policy in Honduras - Newhouse, David Locke (IMF Working Papers; Working Paper ;, 2008)
This paper uses household survey data to estimate the incidence of tax and spending programs in Honduras. Any such exercise is fraught with difficulty, so our simplifying assumptions are carefully explained. Rather than look at tax and spending completely independently, we evaluate net incidence of major programs-such as health care and pensions-to get a more holistic evaluation of redistribution. Our results show that fiscal policy is, on balance, progressive, but that there is room for significant improvement. In particular, energy subsidies, university education and public pension programs provide disproportionate benefits to higher-income households.